2017
DOI: 10.1515/saeb-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support, Stress Coping Behaviors and Mediating Role of Psychological Capital: Special Education and Rehabilitation Centers

Abstract: High level stress in work place is known to be associated with negative organizational behaviors and bad organizational performance. There are individual and organizational factors influencing stress coping behavior of employees. In this study we explore the impact of employees' perceptions of organizational support on their stress coping capabilities (problem-focused stress coping and emotionfocused stress coping) and whether their psychological capital (PsyCap) plays a mediating role in this relationship usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
(88 reference statements)
1
11
1
1
Order By: Relevance
“…Following COR theory, other research (Newman et al, 2018; Roemer & Harris, 2018) have tested the relationship among certain contextual resources (perceived organizational support or POS, perceived supervisor support, and perceived family support), personal support (PsyCap) and employees' psychological wellbeing. Additionally, Erdem et al (2017) found that PsyCap mediated the relationship between POS and emotion‐focused stress coping. Furthermore, Liu et al (2013) found that PsyCap mediated the relationship between POS and depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following COR theory, other research (Newman et al, 2018; Roemer & Harris, 2018) have tested the relationship among certain contextual resources (perceived organizational support or POS, perceived supervisor support, and perceived family support), personal support (PsyCap) and employees' psychological wellbeing. Additionally, Erdem et al (2017) found that PsyCap mediated the relationship between POS and emotion‐focused stress coping. Furthermore, Liu et al (2013) found that PsyCap mediated the relationship between POS and depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…We can conclude that OC could be considered a Psy-Cap antecedent that can include the following identified in the research factors: compassion experienced in the workplace (Ko & Choi, 2019); supportive climate (Luthans et al, 2008c); learning climate (Pitichat et al, 2018); POS (Erdem et al, 2017;Liu et al, 2013;Newman et al, 2018;Pitichat et al, 2018;Roemer & Harris, 2018;Shaheen & Krishnankutty, 2018;Wang et al, 2017); perceived supervisor support (Newman et al, 2018); job autonomy (Mazzetti et al, 2016;Choi, 2020); coworker support (Mazzetti et al, 2016); organizational innovation climate (Hsu & Chen, 2017); and service climate (Kang et al, 2018).…”
Section: Organizational Climate (Oc)mentioning
confidence: 97%
“…In the context of the current global COVID-19 pandemic, the healthcare systems in many countries are under severe pressure; with fewer nurses attending more patients, nurses are facing tremendous physical and psychological pressure. Research has indicated that nurses' job well-being is related to factors such as high work pressure, work satisfaction, and poor organisational management [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of job well-being was proposed by Diener in 1993. It can be used to understand nurses' positive emotional and cognitive evaluation of work (Ge et al, 2012). Job well-being consists of five dimensions: welfare treatment, interpersonal, work value, managers and working characteristics (Erdem et al, 2017). It usually refers to one's shortterm or long-term evaluation of their own life, including positive emotions, negative emotions and life satisfaction (Diener, 2000).…”
mentioning
confidence: 99%